2018
DOI: 10.1128/jvi.00277-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Uncleaved and Mature Human Immunodeficiency Virus Membrane Envelope Glycoprotein Trimers

Abstract: The mature envelope glycoprotein (Env) spike on the surfaces of human immunodeficiency virus type 1 (HIV-1)-infected cells and virions is derived from proteolytic cleavage of a trimeric gp160 glycoprotein precursor. In these studies, we compared the conformations of cleaved and uncleaved membrane Envs with truncated cytoplasmic tails to those of stabilized soluble gp140 SOSIP.664 Env trimers. Deletion of the gp41 cytoplasmic tail did not significantly affect the sensitivity of viruses with the HIV-1 Env to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 126 publications
(100 reference statements)
8
40
0
Order By: Relevance
“…The similarity of these high-resolution Env trimer structures has led to the widely held assumption that these structures represent the pretriggered state 1 conformation. However, differences in the antigenicity, glycosylation, and global architecture of sgp140 SOSIP.664 trimers and functional membrane Envs have been observed (39)(40)(41)(42)(43). Moreover, mutagenesis studies have tested the predictions of the sgp140 SOSIP.664 and EnvΔCT structural models with respect to trimer subunit interactions and failed to obtain the expected Env phenotypes (44)(45)(46).…”
mentioning
confidence: 99%
“…The similarity of these high-resolution Env trimer structures has led to the widely held assumption that these structures represent the pretriggered state 1 conformation. However, differences in the antigenicity, glycosylation, and global architecture of sgp140 SOSIP.664 trimers and functional membrane Envs have been observed (39)(40)(41)(42)(43). Moreover, mutagenesis studies have tested the predictions of the sgp140 SOSIP.664 and EnvΔCT structural models with respect to trimer subunit interactions and failed to obtain the expected Env phenotypes (44)(45)(46).…”
mentioning
confidence: 99%
“…Despite its relatively poor processing, we found that the EnvΔ712 DS mutant could mediate a moderate level of cell-cell fusion in a reducing environment, and this allowed us to investigate the conformation of the functional EnvΔ712 DS glycoprotein. Although these studies were performed with the cytoplasmic tail-deleted EnvΔ712, the ectodomain conformations of the EnvΔ712 and full-length Env from many HIV-1 strains, including HIV-1 JR-FL , are similar (42,101,132). Consistent with this similarity, the unmodified full-length Env and cytoplasmic tail-deleted EnvΔ712 exhibited nearly identical antigenic profiles ( Fig.…”
Section: Discussionmentioning
confidence: 74%
“…The metastability of Env creates immense challenges for structural studies and for the creation of vaccine immunogens. The pretriggered state 1 Env readily transitions into lower-energy conformational states upon removal from its native membrane environment (39)(40)(41)(42). Soluble Env trimers lacking the transmembrane region and cytoplasmic tail are labile and easily dissociate into monomers and dimers (39,(43)(44)(45)(46).…”
mentioning
confidence: 99%
See 2 more Smart Citations